2012
DOI: 10.1063/1.4761473
|View full text |Cite
|
Sign up to set email alerts
|

Bistability patterns and nonlinear switching with very high contrast ratio in a 1550 nm quantum dash semiconductor laser

Abstract: High-power InP quantum dot based semiconductor disk laser exceeding 1.3W Appl. Phys. Lett. 102, 092101 (2013) Chirped InAs/InP quantum-dash laser with enhanced broad spectrum of stimulated emission Appl. Phys. Lett. 102, 091102 (2013) Semiconductor laser monolithically pumped with a light emitting diode operating in the thermoelectrophotonic regime Appl. Phys. Lett. 102, 081116 (2013) Determination of operating parameters for a GaAs-based polariton laser Appl. Phys. Lett. 102, 081115 (2013) GaN-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…To conclude, using a modification of the delay differential mode-locking model proposed in [8][9][10], we have performed a numerical study of the operation regimes of an optically injected semiconductor mode-locked laser. We have shown that similarly to reported experimental results [7,15], bistability and hysteresis can exist between different laser operation regimes. This bistability appears for sufficiently large difference between the linewidth enhancement factors in the gain and absorber sections and is related to overlapping nonlinear resonances corresponding to different longitudinal laser modes.…”
Section: Discussionsupporting
confidence: 88%
“…To conclude, using a modification of the delay differential mode-locking model proposed in [8][9][10], we have performed a numerical study of the operation regimes of an optically injected semiconductor mode-locked laser. We have shown that similarly to reported experimental results [7,15], bistability and hysteresis can exist between different laser operation regimes. This bistability appears for sufficiently large difference between the linewidth enhancement factors in the gain and absorber sections and is related to overlapping nonlinear resonances corresponding to different longitudinal laser modes.…”
Section: Discussionsupporting
confidence: 88%
“…[5][6][7][8][9][10][11][12][13][14][15] Their beneficial operating parameters, like, e.g., low threshold current density and its improved temperature stability, broad wavelength tunability, and high speed of modulation, stem from the properties of the gain medium composed of InAs QDashes grown on InP(001). [6][7][8][9][10][11][12][13][14][15] The InAs/InP(001) material system remains crucial for fabrication of quasi-zero-dimensional semiconductor nanostructures emitting above 1.5 lm. [1][2][3][4][5]8 This may situate the InAs/InP(001) QDashes at the cross point between quantum information processing and optical communication technology.…”
mentioning
confidence: 99%
“…At certain parameters, the interaction can be accompanied by an optical bistability. This phenomenon is a base for the development of all‐optical data processing devices and attracts the interest of many authors 1‐6 . Recently, 7 it was shown that the laser beam longitudinal diffraction plays a fundamental role at the laser pulse interaction with a semiconductor under the appearance of the laser‐induced high absorption domain because this leads to the reflection of laser energy from the domain boundaries.…”
Section: Introductionmentioning
confidence: 99%